Semantic-Forward Relaying for 6G: Performance Boosts With ResNet-18 and GoogleNet Plus - Erkantarci, Betul; Çoban, Mert Korkut; Bozoǧlu, Abdulkadir; Köse, Abdulkadir (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper investigates the integration of advanced deep learning architectures, namely ResNet-18, GoogleNet and enhanced GoogleNet (GoogleNet Plus), into the Semantic-Forward (SF) relaying framework for cooperative communications in 6G networks. The SF relaying framework enhances transmission efficiency and robustness by leveraging semantic information at relay nodes. We analyze and compare the performance of these deep learning models in terms of validation accuracy, semantic accuracy, and Euclidean distance (ED) metrics on the CIFAR-10 dataset. Results indicate that ResNet-18 achieves the highest performance due to its residual learning architecture. GoogleNet Plus, incorporating Automatic Mixed Precision (AMP) training and the Adam optimizer, demonstrates improved stability and efficiency compared to the original GoogleNet. The results highlights the potential of deep learning models to enhance semantic processing capabilities in SF relaying, contributing to the development of more efficient, resilient, and adaptive cooperative communication systems in 6G networks. © 2025 Elsevier B.V., All rights reserved.
IEEE AESS/GRSS Indonesia Section
Keywords: 6 G; Deep Learning; Resilient Access; Semantic Communication; Deep Learning; 6 G; Forward Relaying; Learning Architectures; Learning Models; Performance; Resilient Access; Semantic Communication; Semantics Information; Transmission Efficiency; Cooperative Communication